Food safety training for home industries in Sumber Sari Village, Kutai Kartanegara Regency - Muhammad Fauzan Noor; Surahman Surahman; Karyo Budi Utomo; Ramadhan S. Pernyata; Dini Zulfiani (Community Empowerment, 2022)
This community service's goal is to inform and enlighten the moms of the Family Welfare Empowerment Group (PKK) so they can uphold the quality of processed foods and assist applications for submitting Household Industry Production Numbers (PIRT). The implementation method is carried out with food safety training for home industry products. The program's outcome is an improvement in the partner's skill, which is demonstrated by their acquisition of post-training test points above 60.